Surrogate Mothers: A Radical Feminist Perspective and Regulation in Indonesia - Anna Maria Salamor; Ani Purwanti; Irma Cahyaningtyas (Jurnal Dinamika Hukum, 2026)
A surrogate mother is a woman who agrees to carry a child for a married couple in exchange for compensation. The practice of surrogacy occurs in various countries around the world, both openly and secretly. The purpose of this study is to analyze the practice of surrogate motherhood from the perspective of radical feminist theory and its regulation in Indonesian legislation. The method used is non-doctrinal, with primary data obtained from interviews with informants selected freely and secondary data. The findings of this paper show that radical feminism criticizes and rejects the practice of surrogacy, which is considered to create destructive divisions among women based on social and economic class. The regulation of surrogacy in Indonesian legislation includes the Health Law of 2009 (Amendment 2023), which has not yet been regulated, the MUI fatwa, which prohibits it, and civil law, which considers surrogacy agreements invalid. This article is expected to provide women with a perspective on the practice of surrogacy, which is not always a way out of economic problems, and on the fact that Indonesian legislation does not yet have a strong legal basis for regulating the practice of surrogacy. his study highlights the structural vulnerability experienced by surrogate mothers within patriarchal and capitalist frameworks. It also emphasizes the urgency of establishing clearer and more comprehensive legal regulations to ensure the protection of women’s rights and the legal status of children born through surrogacy practices in Indonesia.